Peripheral blood lymphocytes genetically modified to express the self/tumor antigen MAGE-A3 induce antitumor immune responses in cancer patients - Fontana, Raffaella; Bregni, Marco; Cipponi, Arcadi; Raccosta, Laura; Rainelli, Cristina; Maggioni, Daniela; Lunghi, Francesca; Ciceri, Fabio; Mukenge, Sylvain; Doglioni, Claudio; Colau, Didier; Coulie, Pierre G; et al. (Blood, 2009)
Dendritic cell (DC) targeting in vivo has recently been shown to confer strong and protective cytotoxic T lymphocyte (CTL)-based immunity in tumor murine models. Our group has recently demonstrated in preclinical models that the infusion of genetically modified lymphocytes (GMLs) expressing the self/tumor antigen TRP-2 is able to elicit functional TRP-2-specific effectors with antitumor activity by targeting DCs in vivo. Here we have analyzed vaccine- and tumor-specific immune responses of 10 melanoma patients treated with autologous GMLs expressing the cancer germline gene MAGE-A3. Three of 10 patients treated with MAGE-A3-GML showed an increase of circulating anti-MAGE-A3 T cells, and developed skin delayed-type hypersensitivity to MAGE-A3. Interestingly, in 2 of these patients, with progressive and measurable tumors at study entry, anti-MAGE-A3 T cells were detected not only in the blood but also within tumors resected after vaccination. These results demonstrate that the infusion of MAGE-A3-GML elicits antitumor T cells, which are capable of trafficking to inflamed tissues and of infiltrating tumors. Clinical studies on a larger group of patients are needed to evaluate the clinical efficacy of such a strategy.